Pig Movement and Antimicrobial Use Drive Transmission of Livestock-Associated Staphylococcus aureus CC398 - Tara C. Smith (American Society for Microbiology, 2018)
ABSTRACT The epidemiology of methicillin-resistant Staphylococcus aureus has changed considerably over the last 3 decades, including the recognition of lineages associated with the community and with livestock exposure, in addition to nosocomial strains. A recent study by R. N. Sieber, R. L. Skov, J. Nielsen, J. Schulz, et al. (mBio 9:e02142-18, https://doi.org/10.1128/mBio.02142-18) demonstrates the importance of multisectoral cooperation at the intersection of occupational health, genomics, veterinary medicine practitioners, and farmers in order for us to better understand the epidemiology of antibiotic-resistant organisms.